A Randomized Controlled Trial of the Effects of Febuxostat Therapy on Adipokines and Markers of Kidney Fibrosis in Asymptomatic Hyperuricemic Patients With Diabetic Nephropathy. Issue 1 (December 2016) - Beddhu, Srinivasan; Filipowicz, Rebecca; Wang, Bin; Wei, Guo; Chen, Xiaorui; Roy, Abinash C.; DuVall, Scott L.; Farrukh, Hanadi; Habib, Arsalan N.; Bjordahl, Terrence; Simmons, Debra L.; Munger, Mark; et al.
Background: In observational studies, higher uric acid levels are associated with metabolic syndrome, diabetes, and kidney disease. Objective: The objective of this study is to examine whether reduction of plasma uric acid with febuxostat, a xanthine oxido reductase inhibitor, impacts adipose tissue oxidative stress, adipokines, and markers of systemic inflammation or kidney fibrosis. Design: This was a double-blinded randomized controlled trial. Setting: Academic university setting was used. Patients: Overweight or obese adults with hyperuricemia and type 2 diabetic nephropathy were included. Measurements: Adipose tissue thiobarbituric acid reducing substances (TBARS) and adiponectin concentrations and urinary transforming growth factor–β (TGF-β) were primary endpoints. Plasma C-reactive protein, high molecular weight–adiponectin, interleukin–6, tumor necrosis factor–α, and TBARS and albuminuria were among predefined secondary endpoints. Methods: Participants were randomly assigned to febuxostat (n = 40) or matching placebo (n = 40) and followed for 24 weeks. Results: Baseline plasma uric acid levels were 426 ± 83 µmol/L; 95% completed the study. Estimated glomerular filtration rate (eGFR) declined from 54 ± 17 mL/min/1.73 m 2 at baseline to 51 ± 17 mL/min/1.73 m 2 at 24 weeks ( P = .05). In separate mixed-effects models, compared with placebo, febuxostat reduced uric acid by 50% ( P < .001) but had no significant effects on subcutaneous adipose tissue TBARS (−7.4%, 95% confidence interval [CI], 57.4%-101.4%) or adiponectin (6.7%, 95% CI, 26.0%-53.8%) levels or urinary TGF-β/creatinine ratio (18.0%, 95% CI, 10.0%-54.8%) or secondary endpoints. Limitations: Relatively modest sample size and short duration of follow-up. Conclusions: In this population with progressive diabetic nephropathy, febuxostat effectively reduced plasma uric acid. However, no detectable effects were observed for the prespecified primary or secondary endpoints. Trial Registration: The study was registered inclinicaltrials.gov (NCT01350388).